PENGARUH BIAYA PRIBADI (PRIVATE COST) DAN PERSEPSI SISWA TENTANG PEMBELAJARAN EKONOMI MATERI AKUNTANSI TERHADAP HASIL BELAJAR SISWA SMA - Mawarnia, Beti (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This research aims to (1) analyze the effect of private cost on learning outcomes, (2) analyze the influence of students 'perceptions of the economic lesson on learning outcomes, (3) analyze the effect of private cost and students' perception of economic lesson on towards learning outcomes. This research is an associative causal research with a quantitative approach. Population in this research is the students of XI class majoring in social studies from SMAN 1, SMAN 2 and SMAN 3 Mojokerto year 2013/2014. The type of sampling which used in this study is simple random sampling and the number of samples that used as many as 255 students. The data collection method which used was the method of a questionnaire and documentation. While the methods of analysis using multiple linear regression analysis technique. Based on the results of this study concluded that in partial private cost (X1) significantly affects learning outcomes as well as the students' perception of economic lesson (X2) partially has a significant effect on learning outcomes (Y). While simultaneously the private cost and economic perceptions of students about the learning effect on learning outcomes. From the research that has been described previously, the researchers recommend that students optimizing the allocation of private costs for education and learning have a perception of the economy as a positive study results obtained more optimally